Revestimento comestível para manga (Mangifera Indica, L.) à base de cera de carnaúba com antimicrobianos - Silva, Josiele Brilhante (2009)
The mango crop is one of the principal activities of Brazilian agribusiness. The mango is present in all Brazilian territory, but the economic cultivation is concentrated in the Northeast and Southeast of Bra zil. Among the cultivars of most important commercial, Tommy Atkins is the most cultivated and exported. Most fruits and vegetables have a natural layer of wax on the surface and applying a coating serves to increase the physical, chemical and microbiological stability. The present study aimed to develop edible coatings based on wax added to the antimicrobial triclosan and sorbic acid in order to extend the shelf life of harvested mango ( Mangifera indica L.) variety 'Tommy Atkins. The fruits were subjected to four treatments: mangoes washed and sanitized (control); mangoes washed, sanitized and with carnauba wax (control with wax), mangoes cleaned, sanitized, with waxes and triclosan 1% (carnauba wax with triclosan) and mangoes washed, sanitized, with waxes, and sorbic acid 0.1% (carnauba wax with sorbic acid) for 35 days of storage. The treatments were analyzed using physical, chemical, physico - chemical, microbiological and sensory analysis.